The Characteristic of Sticks Mung Bean Flour (Vigra radiate L.) and The Addition of Celery (Apium graveolens) - Hida Arum Sakura; Nanik Suhartatik; Merkuria Karyantina (JITIPARI, 2023)
Sticks are delicious, crunchy, savory, long, thin, and brownish yellow snacks with various flavors.  The main ingredients of this product consist of wheat flour, , eggs, garlic, pepper, and salt.  Celery leaves were chosen because they are easy to obtain and to optimize local ingredients. Mung bean (Phaseolus radiates) itself is a vegetable food that is high in protein and fiber where the protein contained is 20-25%. This study aims to determine the effect of sticks mung bean flour and the addition of celery.  The design used was a 2 factor factorial completely randomized design (CRD).  Factor 1 is the ratio of wheat flour : mung bean flour  (75:25, 50:50, 25:75) and factor 2 is the concentration of celery porridge (10%, 20%, 30% in 30 ml of water).  The best results of chemical analysis based on the highest protein content were the ratio of wheat flour : mung bean flour 25:75 with concentration of celery porridge 20% with 2.22% water content, 1.74% ash content, 23.58% fat content, 17.75% protein content, 8.28% crude fiber and 46.41 for carbohydrates by difference, color sensory test value 3.73 (greenish brown), crunchy texture 3.40 (crispy), celery taste 3.60 (taste celery flavor) mung bean taste 2.67 (a bit of green bean flavor), celery aroma 3, 33 (smelling of celery), and 3.27 (preferred) for overall liking. The most preferred formulation of celery sticks by consumers is the comparison of wheat flour : mung bean flour 75:25 with the addition of 10% celery porridge concentration with a value of 3.47 (preferred). Sticks made from green beans and celery can be an alternative food that is high in protein and fiber.